Development and Validation of the Motivation for Tutoring Questionnaire in Problem-Based Learning Programs - Salah Eldin, Kassab (2017)
PurposeThere are no published instruments, which measure tutor motivation for conducting small group tutorials in problem-based learning programs. Therefore, we aimed to develop a motivation for tutoring questionnaire in problem-based learning (MTQ-PBL) and evaluate its construct validity. MethodsThe questionnaire included 28 items representing four constructs: tutoring self-efficacy (15 items), tutoring interest (6 items), tutoring value (4 items), and tutoring effort (3 items). Tutors (n=158) from three problem-based medical schools in Egypt, Saudi Arabia and Bahrain rated their perceptions for each item on a 7-point Likert scale. Statistical analyses included examining the factor structure of the questionnaire, the differences between mean scores of each factor as a function of tutoring experience, and the motivation for tutoring scales as predictors of self-rated tutoring skills. ResultsConfirmatory factor analysis indicated that the four-factor theoretical model did not fit with the measurement model. The three items of the tutoring-effort construct were unidentified in the model and four items (three from tutoring self-efficacy and one from tutoring interest) had low regression weights. This ended up with a three-factor structure composed of 21 items representing three main constructs: tutoring self-efficacy (12 items) and tutoring interest (5 items), and tutoring value (4 items). The scores from the 21-item questionnaire demonstrated acceptable fitness indices between the measurement model and the factor structure. Furthermore, the three tutoring motivation subscales demonstrated high internal consistency reliability, significantly correlated with each other and correlated with the self-rated tutoring skills scores. In addition, tutoring efficacy scores significantly increased by years of tutoring experience and predicted 38% of the variance in self-rated tutoring skills scores. DiscussionAnalyzing the tutors’ scores of their motivation for PBL tutoring yielded three significantly correlated constructs representing tutoring self-efficacy, tutoring interest and tutoring value. The findings demonstrated high internal consistency reliability of the questionnaire, strong correlation between the three constructs as well as correlations between the constructs and the self-rated tutoring skills scores. Taken together, the current study demonstrates that the newly developed instrument measuring motivation for PBL tutoring exhibits good psychometric properties. The findings in this paper pave the way for further studies for refining the measurement of this construct in different problem-based contexts.